Análise do componente manejo florestal madeireiro do programa zona franca verde no estado do amazonas: da intenção à ação - Pirani, Alexandre Magalhães (Instituto Nacional de Pesquisas da Amazônia - INPA, 2007)
This project has as objective analyze the strategies and the results reached, from January/2003 to April/2007, in the sustainable forest management topic, of the Amazonas Sustainable Development Program (ZFV, abbreviation in portuguese), of the Amazonas state government. The ZFV had the aim to contribute for the development of the interior town councils on the state in many ways, among them, the sustainable forest management, as a form to raise small producer s income and consequently, their life quality. Due the importance of monitoring and evaluating the implantation process on public policy, this project aimed to evaluate the results reached by the ZFV, the adjustment and effectiveness of the purposed arrangements. And by doing that, contribute to the better aiming of public policy, making it more suitable to the social, cultural and economic reality of the smalls producers in the interior of the Amazon. To reach that, the opinions of diverse actors involved on the formulation and implantation of the program were raised, and so the opinion of the forestall producers supported by the program. This was made by interviews, a workshop, and consulting primary and secondary bibliographic fonts for the raise of historic and quantitative data. The producers were helped by several forms: was created an extension agency for forest area, the AFLORAM, were made some normative adaptations, tax exemption, arrangements between ambient organisms, creation of credit founds and qualification courses. The number of forest management plans rose significantly, but many difficulties arose in the program implantation process, making most of them not been explored. To conclude, public policy implantation process goes far beyond the formulation and implantation of a proposal. The understanding of the many factors that influence the social reality can only be seen during the own process of implantation, consequently, the implantation of a public policy shows itself as an continuous process of decision making, which take some time to generate concrete and large duration results.
Keywords: Amazon; Public Policies; Forest Management; Amazonas Sustainable Development Program; Amazônia; Políticas públicas; Manejo florestal; Amazonas; Programa Zona Franca Verde